The Role of Artificial Intelligence (AI) in Developing Healthcare for Patients (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
AI has entered the healthcare field and has revolutionized it by focusing on accuracy and efficiency in diagnosis and providing comfort to patients, improving treatment plans, and early detection of malignant diseases. AI algorithms, including machine learning, have helped process data more accurately, leading to better and faster prediction of results and enabling them to identify health conditions at the right time. These developments support more efficient treatment plans and simplified medical procedures. In addition, artificial intelligence has helped reduce the cost and effort spent on patient care by providing remote healthcare. As AI tools continue to evolve in the medical field, it is expected to bring about a new era of improved patient care, early detection, and diagnostic accuracy. Despite that the difficulties with data privacy and the requirement for cautious use in medical environments.